Delta-convergence and sequential delta-compactness on Banach spheres (Letters in Nonlinear Analysis and its Applications, 2025)
In this paper, we consider notions of convergence weaker than one with a norm. We call them delta-convergence and dual-delta-convergence, and we investigate the sequential compactness. As an application, we prove a fixed point approximation theorem with the Krasnosel'skii type iterative scheme.
Keywords: Banach sphere; delta-convergence; fixed point approximation